Genetic distance and phylogenetic relationships of Tetraponera rufonigra Jerdon (Hymenoptera: Formicidae) populations in Penang, Malaysia - Faezah Syukriah Sabtu; Abdul Hafiz Ab Majid (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Tetraponera rufonigra, commonly known as the arboreal bicolored ant has gained its notoriety as one of the medically-important pest insects in Malaysia. Tetraponera rufonigra is recognizable by its excruciating sting, causing a severe anaphylaxis especially to those with the history of allergy. The aim of this study was to assess the phylogenetic relationships among the populations of T. rufonigra inferred from 503bp of the mitochondrial DNA Cytochrome Oxidase I (COI) gene. The data obtained were analysed using the T-coffee, ClustalX, MEGA 6.0 and PAUP software. A major monophyletic clade was formed consists of haplotype 1 and haplotype 2. Haplotype 1 consists of samples mostly from industrial areas, differing from the other populations studied by one singleton base. This study will enhance the knowledge about the population’s relationship of T. rufonigra as well as it control and role in fragile ecosystem of Penang, Malaysia.